Multiculturalism and Ethno-Cultural Diversity: Theoretical Insights, Developments and Rising Challenges to the European Migration Policy - Papadakis, Nikos; Dimari, Georgia; Kosmadakis, Nikolaos (HAPSc Policy Briefs Series, 2023)
The present study critically reviews the current theoretical debate on the management of cultural diversity and multiculturalism, emphasizing on the debate between Charles Taylor’s theoretical legacy on “equal worth” and the approach of moral liberalism. Within this context and taking into account the key stakes, the paper proceeds in the brief critical analysis of the European Migration Policy, after the outbreak of the 2015 Refugee Crisis, as well as on the political impact and subsequently the rise of euro-scepticism and anti-migration political agendas and parties (across Europe), based on the instrumentalisation of stereotypes and fears within the European Societies-at-Large. Given the above-mentioned, it also focuses on the rising challenges for the EU Migration Policy.